Henderson Oration: Is open channel flow worth the effort?. Issue 1 (2nd January 2016) - Keller, Robert J.
Abstract: This paper addresses the topic 'Is Open Channel Worth the Effort?' both with respect to the seminal book by Professor Henderson and the discipline of open channel flow. The writer's early contact with Professor Frank Henderson is described. The paper then addresses the topic of open channel flow by reviewing selectively the history of the development of open channel flow and current practice. It is noted that the fundamental principles of continuity, energy and momentum, although developed several 100 years ago, have underpinned the study of open channel flow since their development, and will continue to do so. Over the last 50 years, massive increases in computing power have contributed to very significant advances in our ability to model and understand open channel flow. It is argued that indiscriminant reliance on these models can lead to a reduction, or even total loss, in an understanding of the underlying hydraulic principles. In looking to the future, it is noted that change will continue and that our ability to respond constructively to this change will define our relevance as professionals. It is concluded that both the study of open channel flow and the book by Professor Henderson continue to be very much worth the effort.